Dampak Cyber Attack Bagi Ekonomi Perdagangan Elektronik: Studi Pada Bocornya Data di Platform Tokopedia - Fachri Fadillah; Adelya; Hagi Nur Khanif; Rani Shahira (Fakultas Hukum Universitas Pembangunan Nasional Veteran Jakarta, 2022)
Abstract is typed in Book Antiqua font style Cyber attack is a crime or attack type of offensive maneuver that targets computer information network systems. Crime with the aim of weakening an object in cyberspace has become a crime that often occurs in our daily lives. Social media or even e-commerce is familiar, the more social media is growing, the same thing with crime that continues to follow the times. This has led to an increase in cyber attacks. One example of a cyber attack that occurred in Indonesia recently is the leak of personal data of Tokopedia users on the dark web. So we created this journal article with the aim to find out what is the basis of cyber attack law in Indonesia and how the impact of cyber attacks on e-commerce in Indonesia.